Contexts for Performances of José Lidón’s Oficio de difuntos in 1824: The Exaltation of the Power of Ferdinand VII in Obsequies after the Liberal Triennium - López Ruiz, Luis (Cuadernos de Música Iberoamericana, 2020)
One of the last works composed by José Lidón (1748-1827), chapel master of the Madrid Real Capilla, was his Oficio de difuntos, whose source is preserved in the Archivo General at the Palacio Real. After a general description of the ceremony of royal obsequies at the Spanish court, this article discusses the characteristics of this source and the discrepancy between the dates indicated on it, questioning whether the work was composed in 1821 or in 1824. The different obsequies held in 1824, almost all with strong political connotations and featuring musicians from the Real Capilla, are then examined. It proposes a context for the performance of this Office of the Dead given that, in contrast to other offices written by composers from the Real Capilla after the Peninsula War, José Lidón’s does not give any indication of the occasion for which it was originally composed.